A break with the logic of God’s profit in the perspective of indecent theology - Navernik, Ignac (Poligrafi, 2020)
Marcella María Althaus-Reid defines her theological discourse as a critique of liberation theologies, with an admixture of queer theology. She accuses liberation theologies of establishing a new uniform class of the poor, who have also been deprived of their own reality as liberation theologies were too influenced by western or totalitarian T-theology. The concept of decency is important to South American societies and traditional theology helps to maintain it. In order for true liberation to take place, it must be embedded in the reality of people which in these terms is indecent in that extreme poverty is closely related to sexuality as bodies are the only thing that the poor still possess. There is an aspect that is very present in contemporary Christian theology, especially spirituality: that of God’s profit, i.e., the principle that the total balance of the God/man relationship must be in God’s surplus. It is kind of a transactional relationship that leans toward analogous to bonded labour, which is well seen in the story of Abraham’s bargain with God to spare Sodom and Gomorrah. As opposed to this narrative, there are three images from the life of Jesus which are transgressions of established decency: disciples plucking ears of wheat, thus violating the Sabbath; Jesus’ conversation with the Samaritan woman, where Jesus transcends the established order of interpersonal relationships at the level of gender and religion; and the crucifixion and resurrection, which means a disruption on the existential level. If a profit is one of the main characteristics of the patriarchal-heteronormative construction of society, then God’s complete self-donation in Jesus suggests a final break with the logic of God’s profit. That is liberating for man as it is for the image of God. Indecency is thus inscribed into the Gospel message itself.